One‐Step Covalent Immobilization of β‐Cyclodextrin on sp2 Carbon Surfaces for Selective Trace Amount Probing of Guests. (3rd July 2019) - Li, Zhi; Van Guyse, Joachim F. R.; de la Rosa, Victor R.; Van Gorp, Hans; Walke, Peter; Rodríguez González, Miriam C.; Uji‐i, Hiroshi; Hoogenboom, Richard; De Feyter, Steven; Mertens, Stijn F. L.
Abstract: The modification of solid surfaces with supramolecular hosts is a powerful method to tailor interfacial properties and confer chemical selectivity, but often involves multistep protocols that hinder facile upscaling. Here, the one‐step covalent modification of highly oriented pyrolytic graphite (HOPG) with a β‐cyclodextrin (β‐CD) derivative, which efficiently forms inclusion complexes with hydrophobic guests of suitable size, is demonstrated. The grafted β‐CD‐HOPG surface is investigated toward electrochemical detection of ferrocene and dopamine. The enrichment of the analytes at the electrode surface, through inclusion in β‐CD, leads to an enhanced electrochemical response and an improved detection limit. Furthermore, the modified β‐CD‐HOPG electrode discriminates analytes that form host–guest complexes with β‐CD against a 100‐fold higher background of electroactive substances that do not. Atomic force microscopy, scanning tunneling microscopy, and Raman spectroscopy confirm the covalent nature of the modification and reveal high stability toward solvent rinsing, ultrasonication, and temperatures up to 140 °C. The one‐step covalent modification therefore holds substantial promise for the routine production of inexpensive, yet robust and highly performant electrochemical sensors. Beyond electrochemical sensor development, our strategy is valuable to prepare materials where accurate spatial positioning of functional units and efficient current collection are crucial, e.g. in photoelectrodes or electrocatalysts. Abstract : A simple, one‐step procedure is demonstrated to attach β‐cyclodextrin to a graphite surface. The modified surface can be used as an electrochemical sensor to detect hydrophobic molecules that fit in the cavity of β‐cyclodextrin. Much higher concentrations of hydrophilic molecules, which do not enter the cavity, do not hinder the detection.